Urgensi Pengaturan Mekanisme Pemanfaatan Data Pribadi dalam Rancangan Undang-Undang Perlindungan Data Pribadi - I Wayan Atmanu Wira Pratana (CV Rewang Rencang, 2021)
The protection of personal data is a problem faced by today's global community. The issue of personal data covers various aspects of statehood such as law, politics, and economics. The Cambridge Analytica case in the 2016 U.S. election further encouraged various countries especially Indonesia to try to design legislation to regulate the protection of personal data. Based on the results of the study, there is an urgency of setting the mechanism of the utilization of personal data, both by the government, private companies, and independent institutions. And it is necessary to design a one-door mechanism against the permit and supervision of the utilization of personal data in Indonesia through the establishment of State Auxiliary Organs.